CAPITAL FLIGHT FROM NIGERIA: AN EMPIRICAL ANALYSIS - Musibau Hammed Oluwaseyi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2017)
Capital flight from Nigeria has become a trending macroeconomic issue within the country. This is as a result of its implications on economic growth due to the fall in investment as a result of scarce capital created by persistent capital flight. On estimates, Nigeria losses 22billion to capital flight annually as a result of bad economic system alone; hence the study analyses the impacts of capital flight on Nigeria’s economic growth. The investment portfolio theory is adopted in the study. This posits that an investor considers the real returns from investment in the determination of the retainment of wealth, or otherwise, in a country. Thus, the real interest rates differential has been identified as a main determinant of capital flight in an economy. This study employs the vector error correction mechanism (VECM) and granger causality test to analyse the causality between capital flight, interest rates differential, political instability and economic growth; using available data between 1980 and 2014. The results show that current year capital flight is influenced by its previous year values, and that there is a negative relationship between capital flight and Nigeria’s economic growth. Similarly, the results depict that a positive (and significant) relationship exists between capital flight and interest rates differential, explaining that the higher risk-adjusted returns abroad influence domestic capital flight. Also, there is uni-directional causality running from economic growth to capital flight; while there is independence among other variables.